2019
DOI: 10.3802/jgo.2019.30.e112
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of neoadjuvant chemotherapy plus durvalumab and tremelimumab in advanced-stage ovarian cancer: a Korean Gynecologic Oncology Group Study (KGOG 3046), TRU-D

Abstract: BackgroundA single-arm phase II study of neoadjuvant chemotherapy plus durvalumab and tremelimumab in the treatment of advanced-stage ovarian cancer has begun in Korea. We hypothesized that adding durvalumab (anti-programmed death-ligand 1 antibody) and tremelimumab (anti-cytotoxic T-lymphocyte-associated protein 4 antibody) to chemotherapy in treating this cancer can increase progression-free survival (PFS) with minimal effects on safety.MethodsDuring treatment, serial biopsies will be performed on pre-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“… 107 The Korean Gynecologic Oncology Group has initiated a phase II study (KGOG 346) of neoadjuvant durvalumab and the CTLA-4 inhibitor tremelimumab together with chemotherapy in stage IIIC and IV ovarian cancer. 108 Patients will continue postoperatively with adjuvant chemotherapy and durvalumab and serial biopsies are incorporated in the trial design in order to study biomarkers of response.…”
Section: Immunotherapy Combinations Beyond Parp Inhibitors and Cellulmentioning
confidence: 99%
“… 107 The Korean Gynecologic Oncology Group has initiated a phase II study (KGOG 346) of neoadjuvant durvalumab and the CTLA-4 inhibitor tremelimumab together with chemotherapy in stage IIIC and IV ovarian cancer. 108 Patients will continue postoperatively with adjuvant chemotherapy and durvalumab and serial biopsies are incorporated in the trial design in order to study biomarkers of response.…”
Section: Immunotherapy Combinations Beyond Parp Inhibitors and Cellulmentioning
confidence: 99%
“…Böhm et al [22] suggested that NAC may enhance patients' immune responses, opening a window of opportunity for immune checkpoint inhibitors for patients with advanced-stage ovarian cancer. Based on these results, we began an ongoing clinical trial examining the benefit of combination therapy with conventional chemotherapy, anti-PD-L1, and anti-CTLA-4 to improve the chemotherapy response in NAC [23]. Patients with a low disease burden after NAC who have had a good response to chemotherapy may consider minimally invasive surgery at the time of IDS.…”
Section: Discussionmentioning
confidence: 99%
“…Durvalumab (MEDI4736) is a fully human monoclonal antibody targeting PD-L1 [ 40 ] which improved the OS of patients with advanced NSCLC [ 41 ], advanced urothelial bladder cancer [ 42 ], HNSCC progressed on platinum-based chemotherapy [ 43 ]. Several phase I and phase II studies showed efficacy in triple negative breast cancer [ 44 ] and in advanced-stage ovarian cancer in combination with tremelimumab [ 45 ] or olaparib [ 46 ]. Studies are ongoing.…”
Section: Pd-1 and Pd-l1 Inhibitors In Cancermentioning
confidence: 99%